Diabetes Mellitus and Hypertension are Associated with Bell's Palsy - Romadhoni; Silva Optalmi Herianti; Murwani Yekti; Siti Istiqomah Khamsiyati (Magna Neurologica, 2024)
Background: Bell's palsy occurs in approximately 40-70% of all cases of acute peripheral facial nerve paralysis, and its cause is unknown. Bell's palsy has several risk factors, including diabetes mellitus and hypertension. Objective: This study aims to identify the association between diabetes mellitus and hypertension with the occurrence of Bell's palsy. Methods: This research was conducted at RSUD Tugurejo Semarang in March 2022 using a retrospective study design and purposive sampling technique. Data collected included the history of diabetes mellitus, hypertension, and the occurrence of Bell's palsy. Medical records were used as research instruments. Hypothesis testing was performed using the Fischer exact test. Results: A total of 32 samples were included in this study. There were 11 patients (34.4%) with a history of diabetes mellitus, 21 patients (65.6%) with a history of hypertension, 11 patients experienced acute Bell's palsy (34.4%), and 21 patients had subacute Bell's palsy (65.6%). The statistical analysis showed a significant association between diabetes mellitus (p=0.017) and hypertension (p=0.033) with the occurrence of Bell's palsy. Conclusion: This study reveals a significant correlation between diabetes mellitus and hypertension and the occurrence of Bell's palsy. Several studies also suggest that hypertension is linked to a poorer prognosis in patients with comorbidities and facial paralysis in Bell's palsy. However, there are also studies stating that age and gender are associated with the occurrence of Bell's palsy independently of diabetes and hypertension.